Implementasi Queue pada Sistem Layanan Desa Online “KlikDesa” - Pakpahan, Maissy Angelica; Asra, Naufal Aqiilah; Ginting, Paskal Arienda Epindonta; Arafat, M. Fahmi (Nolsatu Publisher, 2025)
This article discusses the implementation of the queue concept in an online village service system called KlikDesa. The development of this system began with the challenges faced by residents who often had difficulty processing various official documents at the village office due to time constraints. Through KlikDesa, residents can access village administration services online, making the service process more efficient and convenient. The development methods used included needs analysis, system design, and the implementation of a circular queue concept to automatically manage the sequence of service requests. The data used were derived from literature studies and general analysis of village service systems. The implementation results show that the application of the queue concept in KlikDesa helps organize the service flow in a structured manner, reduces waiting times, and increases the efficiency of service requests. Thus, KlikDesa can be a digital solution that supports the transformation of public services at the village level towards a more modern and responsive system.